Gold-catalyzed dimerization of Diarylalkynes: direct access to Azulenes - Claus, Vanessa; Rudolph, Matthias; Rominger, Frank; Xie, Jin; Hashmi, A. Stephen K. (Angewandte Chemie. International edition, 2018)
We have developed a simple gold-catalyzed procedure for the synthesis of substituted and modifiable azulenes. The azulenes are formed either by the dimerization of push-pull diarylalkynes bearing a fluorine atom in ortho or para position or by the dimerization of a symmetric electron-rich diarylalkyne. In the presence of a cationic gold catalyst, the two alkynes can form a highly reactive vinyl cation. Trapping of this high-energy intermediate by an appropriate aryl unit then delivers substituted azulenes in a single step and in a perfect atom economy.
Gesehen am 11.12.2018